Pengaruh ESOP (Employee Stock Ownership Program), Suku Bunga, Kepemilikan Institusional Terhadap Kinerja Keuangan Di Perusahaan Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Riyan Kurniawan Wijaya; Jamaluddin Jamaluddin; Vanessa Putri Johan; Ester Paulina Br. Pasaribu; Hendra Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to examine the influence of ESOP (Employee Stock Ownership Program), Interest Rates, InstitutionalOwnership on Financial Performance in Property and Real Estate Companies listed on the Indonesia Stock Exchange. His research is in theSPSS application. The population in this study were 65 Property and Real Estate Companies listed on the Indonesian Stock Exchange.The sample for this research consisted of35 financialreports. The model is multiple linear regression. The result is that ESOP (Employee StockOwnership Program) and interest rates have no effect on financial performance in propertyand real estate companies listed on theIndonesian Stock Exchange. Institutional Ownership influences Financial Performance in Property and Real Estate Companieslisted on the Indonesian Stock Exchange. ESOP (Employee Stock Ownership Program), Interest Rates, Institutional Ownership influenceFinancial Performance in Property and Real Estate Companies listed on the Indonesian Stock Exchange.